Depressive symptoms and associated factors among pregnant women attending antenatal care at Comprehensive Specialized Hospitals in Northwest Ethiopia, 2022: an institution-based cross-sectional study - Takelle, Girmaw Medfu; Nakie, Girum; Rtbey, Gidey; Melkam, Mamaru (Frontiers in Psychiatry, 2023)
Background: Depression during pregnancy has a significant impact on public health, as it can adversely affect both the mother’s and the child’s health. These can have devastating effects on the mother, the unborn child, and the entire family. Objective: This study aimed to determine the prevalence of depression symptoms and associated factors among pregnant women in Ethiopia. Method: An institutional-based cross-sectional study was conducted among pregnant women attending antenatal care services at comprehensive specialized hospitals in Northwest Ethiopia from May to June 2022. Measurement: The desired data were collected through face-to-face interview techniques by using validated questionnaires such as the Edinburgh Postnatal Depression Scale, the Oslo-3, and the Abuse Assessment Screen tools. The data were analyzed by using SPSS Version 25. Logistic regression analysis was used to identify factors associated with antenatal depression symptoms. Variables having a p-value of less than 0.2 in the bivariate analysis were entered into the multivariable logistic regression. A p-value of less than 0.05 was considered statistically significant, at 95% CI. Results: This study revealed that 91 (19.2%) pregnant women screened positive for depression symptoms. According to multivariable logistic regression, living in rural areas (Adjusted Odds Ratio (AOR) = 2.58, 95%CI: 1.267, 5.256), being at second or third trimesters of gestational age (AOR = 4.40, 95%CI: 1.949, 9.966 and (AOR = 5.42, 95%CI: 2.438, 12.028 respectively), having a history of alcohol use (AOR = 2.41, 95%CI: 1.099, 5.260), having moderate or poor social support (AOR = 2.55, 95%CI: 1.220, 5.338 and AOR = 2.41, 95%CI: 1.106, 5.268) and experience of intimate partner violence (AOR = 2.67, 95%CI: 1.416, 5.016) were the factors significantly associated with depression symptoms at p-value ≤ 0.05. Conclusion and recommendation: The prevalence of depressive symptoms among pregnant women was high. Living in rural areas, second and third trimesters, use of alcohol, having moderate to poor social support, and having a history of intimate partner violence were variables significantly associated with depression symptoms during pregnancy.